EDUCATION MANAGEMENT AND EDUCATION MANAGEMENT IN SMP MUHAMMADIYAH BAYAT KLATEN SPECIAL PROGRAM - Rozik, Muhammad Wakhid (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2020)
The management of educators and education personnel is an activity to manage personnel education that they have to be able to carry out tasks following their functions so that they run effectively. This research aims to deeply understand the management of educators and educational personnel carried out by the principal at SMP Muhammadiyah PK BayatKlaten and to find out the results of the management of educators and education personnel at SMP Muhammadiyah PK BayatKlaten. This study using the type of field research, namely one of the data collection methods in the form of qualitative research. The data coagulation method used is; observation, interviews, and documentation.The results obtained, that the principal in the management of educators and education personnel refer to POAC (Planning Organizing Actuating Controlling). Planning is carried out by implementing a vision and mission, planting Islamic values, and cultivating discipline. Organizing is done by placing it following the competency and making a work team. Actuating is carried out by providing guidance, providing training, and providing welfare. Controlling is done by evaluation and motivation. The results of the management of educators and educational personnel carried out, namely; 1) having high dedication, 2) increasing student achievement, 3) getting the trust of the community, 4) developing learning methods, 5) teacher achievement in both academic and non-academic fields.